Perlindungan Hukum terhadap Data Pribadi dalam Penggunaan Aplikasi Belanja Online (Shopee) - Komang Vena Apriana Dewi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Legal protection of personal data when using online shopping applications, especially Shopee, is becoming increasingly important along with the increasing risk of data misuse. The purpose of this study is to find out the regulations and implementation of personal data protection for Shopee users, especially related to the Paylater function. The study refers to Law Number 27 of 2022 concerning Personal Data Protection and focuses on the challenges faced by consumers related to violations of personal data rights, such as data theft and phishing crimes. The research method used is a normative research method. Consumers' legal awareness of the right to protect personal data is still relatively low, so many consumers d do not take legal action in the event of a violation. This study provides a deeper insight into consumer legal protection in the digital era and serves as a reference for developing more effective policies in protecting the personal data of online shopping application users.